The process of gathering evidence in civil cases: its application in civil and syariah court - Mohamed, Duryana; Abas, Afridah (2009)
The process of gathering evidence is also known as a pre-trial process. Its objective is to gather relevant evidence before the trial. This process is very important since both parties must produce only relevant, reliable and authentic evidence in order to establish a reasonable claim or defence. Nevertheless, in civil court the procedures of gathering evidence seems to be more details and applicable to all types of cases while in syariah court the procedures for gathering evidence is quite limited and confined to limited cases only.